2022
DOI: 10.1002/adhm.202202511
|View full text |Cite
|
Sign up to set email alerts
|

Surface Engineering of Auxetic Scaffolds for Neural and Vascular Differentiation from Human Pluripotent Stem Cells

Abstract: Auxetic materials are the materials that can display negative Poisson's ratio that describes the degree to which a material contracts (or expands) transversally when axially strained. Human stem cells sense the mechanical properties of the microenvironment, including material surface properties, stiffness, and Poisson's ratio. In this study, six different auxetic polyurethane (PU) foams with different elastic modulus (0.7–1.8 kPa) and Poisson's ratio (−0.1 to −0.5) are used to investigate lineage specification… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 74 publications
0
1
0
Order By: Relevance
“…Their findings indicated that auxetic scaffolds notably enhanced PSC differentiation under neural induction conditions [ 25 ]. Collectively, these studies affirm that the unique biophysical properties of auxetic materials can enhance structural capability and foster cell differentiation under specific conditions, offering strategies for designing tissue engineering scaffolds to repair myocardial function [ 26 ].…”
Section: Introductionmentioning
confidence: 90%
“…Their findings indicated that auxetic scaffolds notably enhanced PSC differentiation under neural induction conditions [ 25 ]. Collectively, these studies affirm that the unique biophysical properties of auxetic materials can enhance structural capability and foster cell differentiation under specific conditions, offering strategies for designing tissue engineering scaffolds to repair myocardial function [ 26 ].…”
Section: Introductionmentioning
confidence: 90%